KONTRIBUSI KOMPETENSI SUMBERDAYA MANUSIA TERHADAP KINERJA USAHA KECIL MENENGAH - Chalimah Chalimah; Dian Milasari; Teguh Budi Santoso; Sultoni Sultoni (President University, 2023)
Competence of Human Resources (HR), which is elaborated with Knowledge, Skills, and Capabilities of HR will be able to affect performance in the management of Small and Medium Enterprises (SMEs) in Pekalongan Regency area. The study aims to determine (1) the effect of HR knowledge on the performance of SMEs; (2) The Effect of HR Skills on SME Performance; (3) The Influence of HR Capabilities on SME Performance. This type of research used in this study is causal comparative. The data collection method in this study is a census method using a questionnaire with a population of 250 SMEs, and sample of 60 SMEs. The number of questionnaires that can be processed in this study is as many as 50 MSMEs. The data analysis technique in this study used the classical assumption test, Goodness test, multiple linear regression analysis. The results of this study indicate that: (1) There is a positive influence on HR Knowledge on SME performance with a regression coefficient of 0.161 at a significance of 0.229 and a value of t count t table is 1.808> 1.66543 with a significance value of 0.077.